An Analysis of Madurese Dialect in the English Conversation by the Members of Bata-Bata English Centre (BBEC) - Imroatul Mufidah; Eva Nikmatul Rabbianty (Institut Agama Islam Negeri Madura, 2021)
The concept of world Englishes refers to English as a global language that means communication in numerous dialects and the movement towards an international standard for English. Varieties of English are used in various sociolinguistic contexts in different parts of the world, also in Indonesia. Since English plays as a foreign language, sometimes Indonesians still use their dialect. This study was mainly purposed to describe Madurese dialect in the English conversation made by Bata-Bata English Centre (BBEC). Mainly, this research is aimed to (1) Describe the patterns of Madurese dialect in English conversation by the members of the Bata-Bata English Centre (BBEC). (2) Know the factors that affect the pattern of Madurese dialect in the English conversation by the Bata-Bata English Centre (BBEC). This research belongs to qualitative research which investigates the group of BBEC about Madurese dialect in their English conversation. The researcher observed the students' learning process, interviewed them and took notes, recordings, and pictures. The study results were that the researcher found the patterns of Madurese dialect occur in the English conversation in three features: pronunciation which caused sound changing, a grammatical pattern that caused incorrect grammar; and inappropriate vocabulary. Second, the researcher found that three factors affected how their dialect in the English conversation. The first is lack of speech, Madurese language influences second, and the last factor is never listening to native English speakers. Madurese language that plays as their mother tongue influences their dialect in the English conversation